The commandant of Lubizec : a novel of the Holocaust and Operation Reinhard - Hicks, Patrick (Steerforth Press, 2014)
Tells a documentary-style story of rebellion, survival, and life amid death in a fictitious death camp, shedding new light on the chilling events that took place in 1939 Poland.